- #1

- 264

- 0

## Homework Statement

The curves are:

[tex] y = \frac{x^{4}}{x^{2}+1} [/tex]

and

[tex] y = \frac{1}{x^{2}+1} [/tex]

## The Attempt at a Solution

So again I assume that:

[tex] \frac {x^{4}}{x^{2}+1} = \frac {1}{x^{2}+1} [/tex]

and then cross multiply:

[tex] (x^{2}+1) = x^{4}(x^{2}+1) [/tex]

not really sure at this point if i should distribute the x^4 but if i do it looks like so:

[tex] (x^{2}+1) = (x^{6}+x^{4}) [/tex]

so:

[tex] (x^{2}+1)-(x^{6}+x^{4}) = 0 [/tex]

and I am not really sure what to do at this point, I do have a polynomial if I do the subtraction which is:

[tex] -x^{6}-x^{4}+x^{2}+1 = 0 [/tex]

but I don't know how to factor it....

thanks guys!